Slipcasting. - Wardell, Sasha, ....- (London : A & C Black, 2007)
Best known as one of the most widely used industrial ceramic techniques, slipcasting has become increasingly attractive to individual artists and craftspersons. Slip, a water and clay solution, is poured into porous molds. As the mold absorbs water from the slip, a layer of clay forms a cast. The excess slip is removed from the mold and the cast is stiffened, removed, dried, and fired in a kiln. Since the molds can be based on anything from delicate sculpture to found objects, slipcasting frees artists from the constraints of other ceramic techniques while allowing them to create multiples of their works. Sasha Wardell's Slipcasting is a straightforward, practical guide for those interested in the boundless possibilities of the technique. The book contains more than one hundred color illustrations, diagrams, and slip formulas. An inspiring 'Individual Approaches' chapter discusses the slipcast work of a variety of contemporary ceramicists from around the world.